Resistance training in Obstructive Sleep Apnea: current evidence, limitations, and future directions - Majda, Urszula; Maruszak, Anna; Michalik, Magdalena; Mida, Magdalena; Kwiecień, Julia; Stołtny, Julia; Lisik, Magdalena; Kimla, Witold; Goryczka, Justyna; Hajok, Natalia (Journal of Education, Health and Sport, 2026)
Background: Obstructive sleep apnea (OSA) is a common, sleep-related breathing disorder associated with increased cardiovascular and metabolic risk. Continuous positive airway pressure (CPAP) remains the standard treatment; however, limited adherence and persistent symptoms in some patients caused growing interest in non-pharmacological supportive interventions, including physical activity. The role of resistance training as a distinct intervention in OSA remains poorly defined. Aim: The aim of this narrative review was to summarize current evidence regarding the potential benefits, risks, and practical considerations of resistance training in adult patients with obstructive sleep apnea. Methodology: A narrative review of studies involving adult patients with diagnosed OSA was conducted using major biomedical databases, focusing on resistance training performed alone or as part of combined exercise interventions. Results: Available evidence suggests that resistance training, alone or combined with aerobic exercise, may improve sleep-related breathing parameters, sleep quality, daytime symptoms, muscle strength, and physical function. At the same time, available data highlight potential risks related to transient hemodynamic responses during high-intensity resistance exercise, orthopedic overload, and technique-related breathing disturbances. Conclusions: Resistance training appears to be a promising adjunct to non-pharmacological management of OSA; however further well-designed randomized controlled trials are needed to clarify its long-term efficacy, safety, and optimal training parameters.